Exploring the Potential of Traditional Business Towards 10th SDGs Program: A Case of Sukarara Village, Lombok - Ma'ruf, Aminudin; Tony Seno Aji; Prayudi Setiawan Prabowo; Kukuh Arisetyawan; Wenny Restikasari; Nurul Hanifa; Dita Dismalasari Dewi; Dimas Galih Saputra (Transformatif : Jurnal Pengabdian Masyarakat, 2024)
A tourist village is a location or settlement that offers a tourism experience focusing on culture, nature, or local heritage. One example of a tourist village in Lombok is Sukarara Village, renowned for its traditional weaving industry and traditional Sasak houses. The purpose of this paper is to analyze the potential of Sukarara Village in developing the traditional industry sector and cultural tourism, with a focus on implementing interventions that support economic growth and cultural preservation. The findings reveal that Sukarara Village has significant potential in the traditional industry, particularly in the production of woven fabrics, and offers significant attractions for tourism with its traditional Sasak houses. The results uncover that women in this village play a crucial role in the weaving industry, and collaboration among local stakeholders has contributed to supporting the village's economic growth. The conclusion of this study is that Sukarara Village possesses a substantial economic potential that can be enhanced through synergy between traditional industry and cultural tourism. With effective interventions such as digital promotion and collaboration with tour guide agencies or major events, the village can maximize its economic potential and preserve its culture. Collaboration among various stakeholders, including local government, artisans, tourism professionals, and the village community, is the key to achieving this goal.